2006
DOI: 10.1002/lsm.20336
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence properties of rat cerebellum cortex during postnatal development

Abstract: The results confirm the relationship of the autofluorescence emission properties with histological and biochemical features of biological tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“… 131-133 In this concern, the alteration of the postnatal development of the multilayered rat cerebellar cortex induced by cisplatin administration resulted in an increase in the lipofuscin emission signal and alterations in NAD(P)H and flavin contributions. 132 Actually, cerebellum during development is known to be particularly vulnerable to toxic compounds and radiation, and these findings in response to the cisplatin oxidative damage confirmed that AF-based studies are especially appropriate to investigate the oxidative effects of chemical and physical agent. 134 …”
Section: Lipofuscins and Lipofuscin-like Fluorophores In Aging Oxidamentioning
confidence: 90%
“… 131-133 In this concern, the alteration of the postnatal development of the multilayered rat cerebellar cortex induced by cisplatin administration resulted in an increase in the lipofuscin emission signal and alterations in NAD(P)H and flavin contributions. 132 Actually, cerebellum during development is known to be particularly vulnerable to toxic compounds and radiation, and these findings in response to the cisplatin oxidative damage confirmed that AF-based studies are especially appropriate to investigate the oxidative effects of chemical and physical agent. 134 …”
Section: Lipofuscins and Lipofuscin-like Fluorophores In Aging Oxidamentioning
confidence: 90%